2019
DOI: 10.1038/s41598-019-50311-z
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to simulated microgravity diminishes dendritic cell immunogenicity

Abstract: Immune dysfunction due to microgravity remains a hurdle in the next step of human space exploration. Dendritic cells (DC) represent a critical component of immunity, given their role in the detection of invaders and the subsequent task of activating T cells to respond and eliminate the threat. Upon encounter with microbes, DC undergo a process of maturation, whereby the cells upregulate the expression of surface proteins and secrete cytokines, both required for the optimal activation of CD4+ and CD8+ T cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Another important aspect of RCCS is the rotational speed. Previous studies have reported speeds ranging from 12 to 48 rpm/min, and no universal rotational speed has been identified [ [26] , [27] , [28] ]. Difference in rotational speed may lead to different mechanical stimulation, which can generate diverse cell states.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of RCCS is the rotational speed. Previous studies have reported speeds ranging from 12 to 48 rpm/min, and no universal rotational speed has been identified [ [26] , [27] , [28] ]. Difference in rotational speed may lead to different mechanical stimulation, which can generate diverse cell states.…”
Section: Discussionmentioning
confidence: 99%
“…Since the earliest flights into space in the 1960s, there has been a growing concern about the deleterious effects of exposure to spaceflight environment on human health, among which the immune dysfunction caused by microgravity was clearly defined 1‐8 . Decades ago, nearly half of the astronauts of the Apollo mission acquired infections either during or following their spaceflight, 9 and such an infection has been suggested to manifest only when the immunity is compromised.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, microgravity has been shown to reduce the number, differentiation, and polarization of macrophages by affecting the Rat Sarcoma (RAS)/Extracellular signal-regulated kinase (ERK)/Nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) pathway [6]. Moreover, the dendritc maturation and activation of T-cell is also reduced after prolonged microgravity exposure [7]. On the other hand, microgravity increased the resistance of T-cells to dendritic cell activation [8].…”
Section: Microgravity Effects In Different Tissuesmentioning
confidence: 99%